Zwiedzanie cudzych kolonii. Wiedza i władza w afrykańskich powieściach Karola Maya - Ferens, Dominika (Er(r)go. Teoria - Literatura - Kultura, 2004)
Dominika Ferens Visiting French and German Colonies: Knowledge and Power in Karl May's African Novels This paper considers the ambivalent role that the still popular German writer Karl May (1842-1912) played in the construction of the German colonial discourse. Although May opposed the colonial race and did not travel outside Europe until he was in his sixties, by writing adventure fiction set in exotic locales he colonized the world with his pen. An interesting connection between race, power, and knowledge becomes apparent when we analyze May's "African" novels. At a time when Germany was intent on annexing Namibia, Togo, and Cameroon, May's protagonist is interested only in British and French colonies. He ostensibly travels as an amateur ethnographer yet he already knows Africa better than do the locals. Quick to criticize colonial authorities, he nonetheless repeatedly finds himself in positions of power, authorized by people of color who value his European knowledge. To throw light on May's ambivalent texts, this essay reconstructs their historical context and compares May's flamboyant persona with those of his contemporaries: Sir Richard Burton, Isabelle Eberhardt, and Theodore Roosevelt.